2009
DOI: 10.1901/jaba.2009.42-691
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Tacts Following Mand Training in Young Children With Autism

Abstract: This study sought to examine the effects of training mands on the emergence of tacts with the same response forms. Results indicated that training adjective sets as mands resulted in the emergence of adjective sets as tacts under modified, but not standard, antecedent conditions. The findings suggested that the apparent functional independence of mands and tacts may be explained by a lack of appropriate antecedent control over responding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
18
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 6 publications
7
18
0
2
Order By: Relevance
“…Specifically, the initial functional independence observed in standard antecedent conditions during posttraining probes was subsequently overcome by the introduction of the modified antecedent. Notably, these findings are consistent with previous research indicating that antecedent conditions control the emergence of untrained mand or tact operants following training in the other operant (Egan & Barnes-Holmes, 2008, 2009). The authors concluded that the modified antecedent functioned as a verbal discriminative stimulus that cued participants to respond in the context of the experimental conditions.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Specifically, the initial functional independence observed in standard antecedent conditions during posttraining probes was subsequently overcome by the introduction of the modified antecedent. Notably, these findings are consistent with previous research indicating that antecedent conditions control the emergence of untrained mand or tact operants following training in the other operant (Egan & Barnes-Holmes, 2008, 2009). The authors concluded that the modified antecedent functioned as a verbal discriminative stimulus that cued participants to respond in the context of the experimental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the form of the verbal SD determined the emergence of mands for these participants. This finding is consistent with previous research demonstrating that the form of antecedent SD presented during mand probes may control emergent responding (Egan & Barnes-Holmes, 2008, 2009. Thus, future research should consider the form of the SD employed during emergent mand probes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations